Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Could someone give me the consecutive steps to derive the following equations:

$$P(Y=1) = \frac{\mathrm{OR}}{1+\mathrm{OR}}$$


$$P(Y=0) = \frac{1}{1+\mathrm{OR}}$$



where $P(Y=1)$ is the probability of success, $P(Y=0)$ is the probability of failure, and $\mathrm{OR}$ is the Odds Ratio.

It should have something to do with the fact that $P(Y=1) + P(Y=0)=1$, but I can't work it out.

share|cite|improve this question
1. substitute $OR = P(Y=1)/P(Y=0)$ in any of the equation that you have to derive $\phantom{x}\\$ 2. when deriving the equation for $P(Y=1)$ substitute $P(Y=0)=1-P(Y=1)$ $\phantom{x}\\$ 3. simplify – Ilya Jan 11 '13 at 10:01
Thanks. But isn't that using the solution to get to the solution? I mean, could I do it without making use of the derivations yet in step 1. – Marloes Jan 11 '13 at 10:11
up vote 0 down vote accepted

This is just two equations with two unknowns $$ c=\frac{a}{b},\qquad a+b=1, $$ where $a,b\in (0,1)$ and $c\in (0,\infty)$.

Let us solve for $b$. The first equation yields $a=bc$, and substituting this into the second equation yields $$ 1=bc+b=b(c+1)\quad\Rightarrow \quad b=\frac{1}{c+1}. $$ Now use that $a=1-b$ to derive an expression for $a$ depending only on $c$, and realize that your example has $a=P(Y=0)$, $b=P(Y=1)$ and $c=\mathrm{OR}$.

share|cite|improve this answer
Thanks, So that last step would be $a=1-(1/c+1)$ How does that give $a=c/1+c$ – Marloes Jan 11 '13 at 10:34
Try to write $1$ as $\frac{c+1}{c+1}$ and put the two fractions together. – Stefan Hansen Jan 11 '13 at 10:36

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.